Comparative Evaluation of Immediate Versus Delayed Antibiotic Prescription in Pediatric Acute Otitis Media - Irshad Ali, Arzoo Akram, Salman Ahmed Niaz Mangrio, Abdul Ghafoor, Misbah Munir, Javed Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute otitis media (AOM) is one of the most common pediatric infections and a leading cause of antibiotic prescriptions. As a result of concerns about antibiotic resistance and adverse effects, delayed antibiotic prescribing as an alternative to immediate therapy has been of interest. In this study, immediate versus delayed antibiotic treatment in children with uncomplicated AOM was compared in terms of clinical efficacy, inflammatory response and safety. Methods: This is a prospective, multicenter study in which, from January 2022 to January 2023, the University Medical College, Islamabad, the Children’s Hospital, Taif, and the Children’s Hospital, Lahore, enrolled 150 children aged 6 months to 12 years with a clinically diagnosed AOM. We proceeded with nonrandom patient assignment to receive either immediate (n = 75) or delayed (n = 75) antibiotic therapy. Demographics with baseline age, weight, and sex, and inflammatory biomarkers (C-reactive protein [CRP] and white blood cell [WBC] count) were recorded. The primary end point was complete symptom resolution by day 7, and the secondary end points were total antibiotic usage, adverse events, reconsultation rates, and complications. Results: Groups were similar on baseline characteristics. On day 7, the immediate group was 89.3% and the delayed group was 80.0%, and achieved complete symptom resolution (p > 0.05). Thus, the antibiotics were given to all patients in the immediate group, but only 36 percent of the delayed group needed treatment. There were 28% of the immediate group and 14.7% of the delayed group with adverse events. CRP and WBC counts were significantly reduced from baseline in both groups, with no significant between-group difference. Conclusion: Clinical outcomes of delayed antibiotic prescribing for uncomplicated pediatric AOM are equivalent to immediate therapy and provide reductions in antibiotic exposure and adverse events. This approach facilitates the development of improved antimicrobial stewardship in pediatrics. Keywords: acute otitis media, pediatric, delayed antibiotic, immediate antibiotic, antimicrobial stewardship, CRP, WBC, antibiotic resistance